(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The adoption of more efficient management practices, such as recognizing the adequate level of P availability (Olsen) in the soil, can result in improved production efficiency in the carrot (Daucus carota L.) cropping system. Complementarily, knowing the behavior of radiation use efficiency (EUR) is relevant in the optimization of resources (Pfertilizer and radiation), due to the continuous concern for environmental impact and for the reduction of production costs. The objective of this work was to evaluate the EUR performance of two commercial carrot cultivars, across five levels of P-Olsen availability, under field conditions (13, 16, 19, 24, 28 ppm). The experiment was established at the Santa Rosa Experimental Station (39º47’S; 73º14’W), belonging to the Universidad Austral de Chile (UACh) located in the city of Valdivia in the Los Ríos Region, during the 2010-2011 growing season. EUR (g DM MJ-1) was calculated using photosynthetically active radiation (RIFA) and biomass (aerial and total). In this study, EUR of D. carota cultivars was not influenced by soil P-Olsen availability (p>0.05), but differences (p<0.01) were found in photosynthetically active radiation intercepted (RIFA) and specific leaf area.